Outline for the course in organization of library materials - Frick,Bertha M; Tauber,Maurice F (New York : School of Library Service, 1958)
The outlines contains in this syllabus were selected to accommodate ideas by student on the basic concepts and traditional practices, and present -day criticisms on the organization of library materials.
Includes bibliographical references
obn 22/01/2019
Loans
Keywords: Library operations-role and function